Ludicidade, artesanias pedagógicas e ambiências bioecológicas produzindo a educadora infantil artífice do seu ofício - Strappazzon, Janaína Schock (2023)
This Dissertation is part of Line of Research 1 - “Teaching, knowledge and professional development”, of the Graduate Program in Education at the Federal University of Santa Maria (UFSM) - Master's Degree in Education. It presents as the main question of the research: How does the kindergarten teacher reinvent herself in the process of educating as an artisan of her craft and through playfulness, pedagogical crafts and exploratory bioecological ambiences? The PPCT Paradigm and Bioecological Model (Process-Person-Context-Time), proposed by Bronfenbrenner and Morris (1998), helped the epistemological and conceptual construction of the developing person, structuring the autobiographical approach of the kindergarten teacher and the conception of Early Childhood Education , with an emphasis on educating babies and very young children. Regarding the methodological process, the research covered the Systematic Literature Review (SLR), contributing to the theoretical corpus of the research and adding the current scope of the issue in academic works (dissertations and theses) on the continuing education of Early Childhood Education teachers. In a second moment, the documental study was projected in the cultural macrosystem and in the public policies aimed at Early Childhood Education (covering the National Common Curricular Base - BNCC EI) and, in the same way, to show the cultural singularities of the study scenario and its protagonists. The theoretical-conceptual configuration articulates: the Paradigm/Model and the Bioecology of Human Development, proposed by Urie Bronfenbrenner; the kindergarten teacher, craftsman of her craft, from Richard Sennett, Andrea Alliaud and Paulo Freire. Expanding the specificity of Early Childhood Education, from the perspective of stimulating the child's autonomous growth, Emmi Pikler, respecting the natural development of physical, psychological and social skills and, finally, the heuristic play approach for working with young children, proposed by Elinor Violet Goldschmied, which is a different method for planning activities for children in early childhood. Dissertation writing is characterized as a selfnarrative, approaching (auto)biographical research. Talking about oneself through memoriesreferences, symbolizes what the author understands as constitutive elements of her (self) formation, showing images of ambiences played by children. Exploratory bioecological ambiences promoted relational processes with the environment, culture and history, starting long before the child explored space. It starts with the planning of ideas based on what was observed in the processes already experienced, the selection of materials and the possibilities organized with the sensitivity of the educator and the exchange she has with her peers, when dialoguing about the possibilities and exploratory and sensorial gains. Before conceiving an ambience, one takes the axes and codes in the references; one chooses the best spaces - whether external or internal; the best strategies for exploring the group are studied, since it is the children who really play a leading role in the bioecological environment, interacting in a playful way. These learning experiences are unique and unpredictable, and with children, magic exists, and that is professional self-realization in Early Childhood Education.